Parental Support and Career Ambivalence: A Study of Vocational High School Students in Yogyakarta - Natsir, Humairah; Harahap, Dewi Handayani; Rizqia, Ayu Gigih (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Career indecision is a common challenge faced by vocational high school (SMK) students as they transition to the workforce or higher education. One contributing factor is parental support. This study aims to examine the relationship between parental support and career indecision among 12th-grade students at SMK Koperasi Yogyakarta. Using a quantitative correlational descriptive design, the study involved 88 students as the total population. The instruments used were Likert-scale questionnaires tested for validity and reliability, with Cronbach’s alpha of 0.927 for parental support and 0.759 for career indecision. Data were analyzed using descriptive statistics, classical assumption tests, Pearson correlation, and partial correlation with SPSS version 23. The results showed a significant negative correlation between parental support and career indecision (r = -0.381; p = 0.005). Moreover, partial correlation analysis revealed that only the informational support aspect had a significant relationship with the lack of information aspect in career indecision (r = 0.328; p = 0.023). These findings highlight the importance of informational parental support in assisting students in making informed career decisions.Kebimbangan dalam memilih karier (career indecision) merupakan tantangan umum bagi siswa Sekolah Menengah Kejuruan (SMK) dalam menghadapi transisi ke dunia kerja atau pendidikan tinggi. Salah satu faktor yang memengaruhi kebimbangan tersebut adalah dukungan orangtua (parental support). Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan orangtua dan kebimbangan memilih karier pada siswa kelas XII SMK Koperasi Yogyakarta. Penelitian ini menggunakan pendekatan kuantitatif dengan desain deskriptif korelasional, melibatkan 88 siswa sebagai subjek studi populasi. Instrumen yang digunakan adalah skala Likert, yang telah diuji validitas dan reliabilitasnya dengan koefisien alpha sebesar 0,927 untuk skala dukungan orangtua dan 0,759 untuk skala kebimbangan karier. Analisis data dilakukan menggunakan statistik deskriptif, uji asumsi klasik, serta korelasi Pearson dan korelasi parsial dengan bantuan SPSS versi 23. Hasil menunjukkan terdapat hubungan negatif yang signifikan antara dukungan orangtua dan kebimbangan karier (r = -0,381; p = 0,005). Selain itu, uji korelasi parsial mengungkap bahwa hanya aspek dukungan informasional orangtua yang berkorelasi signifikan dengan aspek kekurangan informasi dalam kebimbangan karier (r = 0,328; p = 0,023). Temuan ini menekankan pentingnya peran orangtua, khususnya dalam memberikan informasi terkait pendidikan dan karier, untuk membantu siswa membuat keputusan yang tepat.